2009
DOI: 10.1139/b09-058
|View full text |Cite
|
Sign up to set email alerts
|

Spatial genetic structure of lowbush blueberry,Vaccinium angustifolium, in four fields in Maine

Abstract: Expressed sequence tag -polymerase chain reaction (EST-PCR) molecular markers were used to infer spatial genetic structure of four lowbush blueberry (Vaccinium angustifolium Ait.) fields in Maine. Genetic structure was quantified at three spatial scales: (1) within apparent clones (intrapatch), (2) among clones within a field, and (3) among fields separated by as much as 65 km. Of five ''clones'' or putative individuals examined in the intrapatch study, two showed complete genetic homogeneity within the patch,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
53
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 56 publications
9
53
0
Order By: Relevance
“…Forests are harvested and the existing understory blueberry plants become established.The underlying genetic diversity of lowbush blueberry is relatively unknown compared to other fruit crops [8]. Recently, a variety of techniques and molecular markers have been used to investigate the genetic heterogeneity and relatedness of V. angustifolium populations [1,8,[10][11][12][13][14][15]. These studies have shown V. angustifolium to be highly diverse in Maine and the Canadian Maritimes.…”
mentioning
confidence: 99%
“…Forests are harvested and the existing understory blueberry plants become established.The underlying genetic diversity of lowbush blueberry is relatively unknown compared to other fruit crops [8]. Recently, a variety of techniques and molecular markers have been used to investigate the genetic heterogeneity and relatedness of V. angustifolium populations [1,8,[10][11][12][13][14][15]. These studies have shown V. angustifolium to be highly diverse in Maine and the Canadian Maritimes.…”
mentioning
confidence: 99%
“…Paired shoots were determined to originate from the same clone by following the shoot to the crown of the clone. Clones were also differentiated from one another based on morphology and growth pattern (Bell et al 2009). For each clone two pollination treatments were compared: (1) an open-pollinated inflorescence (i.e., pollinated by managed and native pollinators present in the field), and (2) an inflorescence supplementally pollinated by hand with outcross pollen collected from a separate clone located at least 5 m away from the experimental transect (Table 1).…”
Section: Study Areamentioning
confidence: 99%
“…However, the large clone size of lowbush blueberry (commonly 2-10 m in diameter; Bell et al 2009, Bobiwash et al 2013) and the simultaneous display of thousands flowers on a clone increases the likelihood of selfpollen transfer by pollinators that forage on flowers within a clone (Eckert 2000, Charpentier 2001, Barrett 2002, 2003, and so it is unclear whether augmenting numbers of native pollinators by introducing non-native pollinators, as commonly practiced by growers, is sufficient to increase yields.…”
Section: Introductionmentioning
confidence: 99%
“…Natural dispersal of both pollen (bees) and seed (birds and bears) has resulted in the pronounced patterns of genetic diversity evident today. The species is highly polymorphic at the morphological, physiological, and molecular levels (Vander Kloet 1978;Bell et al 2008Bell et al , 2009). Lowbush blueberry is, to a large extent, self-infertile (Aalders and Hall 1961); however, the degree of self-fertility can vary greatly among individuals (Wood 1968;Bell et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…If, indeed, some clones are functioning as males and produce few ovules or seed, this could be an additional explanation for variations in clonal yield, a topic that we have been studying for several years (Bell 2009;Bell et al 2010). For male fertility, we measured the same trait as Myra (2004), viable microspores per flower (number of pollen tetrads per flower × 4 × proportion pollen viability).…”
Section: Introductionmentioning
confidence: 99%